Investigation and Analysis of Physical transformations of Mashhad urban complex using chaos theory (Mashhad Metropolis, Toos and Binalood Area) - Mohammad Homaiefar (تحقيقات جغرافيايی, 2020)
Aim @ Backgrounds: Physical texture of urban areas can have chaotic behavior due to their non-linear and unpredictable characteristics. The theory of chaos in urban development attempts to explore physical development which has fractal geometry, as a non-linear, sensitive to preliminary conditions and generalizable to different scales with an emphasis on geometric aspects of it. In this study, with the aim of achieving the physical growth pattern, the physical status of a part of Mashhad urban complex has been investigated and analyzed as a coherent whole with homogeneous function (tourism). Methodology: The research method in this study is analytical-descriptive. In order to achieve the goals of the research, the urban fabric of a designated area has been studied with the help of up-to-date maps and specialized software. Scaling has been adhered to as a generalizable process, In the process, Therefore, this research is one of the applied research. Findings: With respect to scaling, the correlation coefficient between the geometric parameters indicates a significant relationship between these parameters. The fractal spectrum of the study area at various scales (whole and component) indicates the autopsy of the study body and describes its process. Conclusion: As a result, physical growth process in the studied area is chaotic and it follows a specific growth pattern at different scales. Far from the populated cores (Mashhad, Toos, Torghabeh and Shandiz),physical  geometry tends to be linear, and it is also in relation to transport arterieschr('39') geometry.